Community development transformation of Cooper neighborhood: a Rutgers-Camden University and LEAP Academy school collaboration through sustainable development. Issue 5 (19th October 2020) - Bonilla-Santiago, Gloria
ABSTRACT: Comprehensive community initiatives integrating holistic educational approachs for children and families are vital to building and sustaining 100% high school graduation rate in a distressed urban setting. Despite numerous social, economic, and cultural barriers, the Rutgers-Camden University and LEAP Academy partnership has not only provided hundreds of children with a comprehensive education and access to opportunities, but it has also empowered them and their families as individuals. This university-driven community development intitiaitve was able to trasnform the entire city oif Camden, NJ through the expansion of an integrated pipeline model that prepared students, trained families and nurtured neighboring communities. Utilizing a case study methodology and appreciative inquiry framework, this study explores these university-driven programs when community members are included in the planning stages and are benficieries in the operations and governance. This collaborative case study provides many insights into best practices that can be upscaled within other community-based educational models.